Innocence killed: Role of propaganda videos in the recruitment of children of the Islamic State of Iraq and Syria. - Khoo, Flora; Brown, William J. (Journal of International Communication, 2021)
Children of ISIS have no childhood. They are exposed to extreme violence and targeted by ISIS for recruitment. This study examines the role of ISIS child propaganda videos in catalysing the process of radicalising and recruiting children to join the Islamic State. Sixty in-depth interviews of Syrian families and children who have been exposed to ISIS propaganda show that children join ISIS mainly for survival. When they join the Islamic State, they are given a new identity. Fishers' narrative paradigm provides the theoretical grounds for understanding the appeals ISIS' creates through its narratives in their propaganda videos. The present research demonstrates how the narrative of the glorification of heaven draws potential martyrs and how families shape a key part of the Islamic State's narratives used to recruit children.